Emigracyjna „epistolomania” (na marginesie listów Jana Lechonia i Kazimierza Wierzyńskiego) - Osiński, Jakub (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
The review devoted to the epistolography of Polish emigration in the last century on the example of correspondence between Jan Lechoń and Kazimierz Wierzyński, issued by Beata Dorosz and Paweł Kądziela (Warsaw 2016). The author presents the main problems with the correspondence of emigrants in the context of biographies and history, and analyzing the issue of Lechoń and Wierzyński letters.